2018
DOI: 10.1021/acssuschemeng.8b03597
|View full text |Cite
|
Sign up to set email alerts
|

Amine-Grafted MIL-101(Cr) via Double-Solvent Incorporation for Synergistic Enhancement of CO2 Uptake and Selectivity

Abstract: Recent research on the amine-grafted metal−organic frameworks has obviously spurred intriguing application prospects in the field of CO 2 capture; however, few of them focused on the synthetic approach, which directly determines their structural stabilities for the application. This work explores a double-solvent incorporation strategy to rapidly squeeze the molecule-level amines into the cavites of MIL-101(Cr) without any framework destruction of MOFs. Tris(2aminoethyl) amine (TAEA), ethylenediamine (ED) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…S11, the derived Q st value for MIL-101(Cr) (19 kJ mol −1 ) at low surface coverage is quite accordance with the existing literature 48,49 . Upon RHA incorporation, the Q st value was increased slightly for RHA-MIL-101(Cr)-I (20 kJ mol −1 ) and RHA-MIL-101(Cr)-II (30 kJ mol −1 ) at low surface coverage, attributed to the strong electrostatic interaction for CO 2 with narrow pore size distribution 49 . Notably, the Q st value of RHA-MIL-101(Cr) is at par with the several established MOF based composites available in the literature (Table S3).…”
Section: Resultssupporting
confidence: 87%
“…S11, the derived Q st value for MIL-101(Cr) (19 kJ mol −1 ) at low surface coverage is quite accordance with the existing literature 48,49 . Upon RHA incorporation, the Q st value was increased slightly for RHA-MIL-101(Cr)-I (20 kJ mol −1 ) and RHA-MIL-101(Cr)-II (30 kJ mol −1 ) at low surface coverage, attributed to the strong electrostatic interaction for CO 2 with narrow pore size distribution 49 . Notably, the Q st value of RHA-MIL-101(Cr) is at par with the several established MOF based composites available in the literature (Table S3).…”
Section: Resultssupporting
confidence: 87%
“…Except for its distinct merits such as large pore volume, high BET surface area, and excellent stability in water, MIL-101 also contains numerous potential open chromium sites (up to 3.0 mmol/g) (Hwang et al, 2008) with an unoccupied orbital that are expected to anchor amine functionalization via a strong binding interaction with the positive nitrogen atoms. It is also demonstrated that amine-functionalized MIL-101 has high CO 2 capture capacities (Lin et al, 2013; Yan et al, 2013; Hu et al, 2014; Lin J.-L. et al, 2014; Cabello et al, 2015; Darunte et al, 2016; Huang et al, 2016; Emerson et al, 2018; Zhong et al, 2018; Liu et al, 2019). Thus, in our work, MIL-101(Cr) was fabricated and modified with a series of amines to achieve the efficient storage of CO 2 substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Further FT‐IR spectra prove the existence of organic molecules in the framework, as the distinct C‐N adsorption peak can be observed (Figure S5, Supporting Information). [ 18 ] Element analyses of C and N were conducted to compare the quantity of different Lewis bases in the framework: The calculated molar ratios of Cr 3+ /Lewis base are 1.23, 1.73, and 3.15 for MIL‐101(Cr)‐imidazole, MIL‐101(Cr)‐DETA, and MIL‐101(Cr)‐PEHA, respectively. From the TGA results (Figure S6, Supporting Information), the weight loss below 100 °C is due to the elimination of free guest molecules, and the coordinated H 2 O molecules on metal clusters in the MOFs will be eliminated only at higher temperature (100–200 °C).…”
Section: Resultsmentioning
confidence: 99%